2019
DOI: 10.1007/s11064-019-02722-7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mating and the Male Sex Peptide on Group Behaviour of Post-mated Female Drosophila melanogaster

Abstract: Sleep is a highly conserved state in animals, but its regulation and physiological function is poorly understood. Drosophila melanogaster is an excellent model for studying sleep regulation and has been used to investigate how sex and social interactions can influence wake-sleep profiles. Previously we have shown that copulation has a profound effect on day time activity and quiescence (siesta sleep) of individual post-mated females. Here we have the studied the effect of mating and the transfer of the 36 amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
(101 reference statements)
0
4
0
Order By: Relevance
“…A limited analysis of possible behavioral differences between winter and summer morph flies was included for April semifield and corresponding laboratory mimic conditions based on the rationale that a mixture of summer and winter morph flies may be present at this time of year within the United Kingdom. Moreover, as differences in the Drosophila female reproductive state have been reported to affect locomotor activity (Ferguson et al, 2015; Isaac, 2019), we hypothesized that analogous differences might be observed between reproductively active summer morph flies and winter morph flies that have entered reproductive diapause. As described above (in the Materials and Methods section), reproductive quiescence was, indeed, confirmed for the winter morph flies prior to their use in our behavioral analyses.…”
Section: Resultsmentioning
confidence: 96%
“…A limited analysis of possible behavioral differences between winter and summer morph flies was included for April semifield and corresponding laboratory mimic conditions based on the rationale that a mixture of summer and winter morph flies may be present at this time of year within the United Kingdom. Moreover, as differences in the Drosophila female reproductive state have been reported to affect locomotor activity (Ferguson et al, 2015; Isaac, 2019), we hypothesized that analogous differences might be observed between reproductively active summer morph flies and winter morph flies that have entered reproductive diapause. As described above (in the Materials and Methods section), reproductive quiescence was, indeed, confirmed for the winter morph flies prior to their use in our behavioral analyses.…”
Section: Resultsmentioning
confidence: 96%
“…All females used in our experiments were kept with males, therefore were likely mated. Sex peptides transferred from males dramatically alter female sleep behavior, and these sex-specific differences in temperature response may be caused by evolution in sex peptide genes [ 46 , 47 ]. Along with sex peptides, changes in splicing of circadian clock genes can regulate responses to seasonal changes in temperature and photoperiod [ 44 ], and temperature-induced changes in day sleep are regulated by clock genes [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Marginally reduced photophobia among mated females relative to unmated females, independent of mite exposure, may represent increased exploratory behaviour while searching for ovipositing sites [32]. Furthermore, copulation per se can alter the behaviour of female flies [39,40]. For example, copulation increases Drosophila dispersiveness [39].…”
Section: Discussionmentioning
confidence: 99%